Wpływ uregulowań prawnopodatkowych na ochronę rodziny - Masior, Michał (Kwartalnik Prawa Podatkowego, 2015)
The article assesses Polish tax law with regards to the principle of family protection established in the Constitution. Drawing from the literature and the statutes the author provides an overall picture of the stipulations, which refer to or are supportive of family. Some of them serve more general social functions. Personal income tax and inheritance and donations tax are best suited to realize family policy goals. Value added tax and excise tax can at most contain only some general socially motivated elements. The analysis is complemented by the general comments on possible family-serving solutions absent in the tax law and the provisions, which penalize family ties.